Gene profiling of in vitro and in vivo models of delayed neutrophil apoptosis: a common pathway?. (1st June 2004) - O'Neill, A.; Greenan, M.C.; Doyle, B.; Fitzpatrick, J.M.; Watson, R.W.G.
Abstract : Mechanisms responsible for the termination of an inflammatory response include the activation of a genetic programme of cellular suicide termed apoptosis, which leads to the elimination of the cellular effectors of acute inflammation, particularly the neutrophil. However, delays in this response result in the persistence of inflammation and the development of inflammatory disorders. Understanding the mechanism that inhibits the process of cell death may be helpful in the treatment of inflammatory disorders. Inflammatory cytokines have been shown to inhibit apoptosis through stabilization of the mitochondria and inhibition of the caspase cascade. To date, how these processes are inhibited remains the central question. We hypothesize that the decision for the delay in neutrophil apoptosis is made through signals delivered on the cell surface, which activate combinations of specific genes that inhibit the cell death pathway. Gene chip microarray experiments were performed in in vivo and in vitro models of delayed neutrophil apoptosis. Analysis has yielded changes in a large number of genes involved in inflammation, metabolism, signalling, mitochondrial function and apoptosis. A number of genes have been identified as suitable targets responsible for the regulation of neutrophil apoptosis and their expression was confirmed by real-time PCR and explored at the level of the protein. Their functional role in the apoptotic response is now being determined. One significant finding is that the gene patterns of delay in vitro and in vivo appear to be different, indicating the possibility for different pathways regulating the delay in neutrophil apoptosis.